Molecular Effects of Treatment of Human Colorectal Cancer Cells with Natural and Classical Chemotherapeutic Drugs: Alterations in the Expression of Apoptosis-related BCL2 Family Members, Including BCL2L12 - Kontos, Christos K.; Avgeris, Margaritis; Vassilacopoulou, Dido; Ardavanis, Alexandros; Scorilas, Andreas (Current Pharmaceutical Biotechnology, 2018)
Background: Current chemotherapy regimens for the treatment of colorectal cancer (CRC) include oxaliplatin, irinotecan, and fluorouracil along with leucovorin. Cytotoxicity involves the induction of programmed cell death. Objective: The purpose of this study was to assess the molecular effects of doxorubicin (a 14-OH derivative of the natural product daunorubicin) and common chemotherapeutic drugs (used in the clinical practice to treat CRC) on the expression of the most prominent members of the BCL2 family, namely BCL2, BAX, BCLX, and MCL1. Moreover, we sought to define the role of BCL2L12, another member of the BCL2 family, the apoptotic role of which is ambiguous. Methods: The MTT cell proliferation assay was used to determine the IC50 of each chemotherapeutic drug at 72 hours of treatment of Caco-2 and DLD-1 colorectal adenocarcinoma cell lines. Real-time PCR was used to quantify the antiapoptotic BCL2-α, BLCX-L, and MCL1-L transcripts, the proapoptotic BAX, BLCX-S, BLCX-ES, MCL1-S, and MCL1-ES transcripts, and BCL2L12 expression in relation to GAPDH mRNA levels. Results: We constructed growth curves of Caco-2 and DLD-1 cells and determined the IC50 of each drug at 72 hours of treatment. Significant alterations in the expression levels of the studied BCL2 family genes and/or particular transcripts were observed. Conclusion: The intrinsic apoptotic pathway is activated during treatment of CRC cells with common chemotherapeutic drugs. Moreover, BCL2L12 mRNA expression increases progressively during treatment, similarly to the expression of other BCL2 family genes favoring apoptosis and/or particular proapoptotic transcripts, thus suggesting a proapoptotic role for BCL2L12 in chemotherapy-treated CRC cells.
Keywords: programmed cell death